Implementing of Limited Face-to-Face Learning Policy in Schools - Sugiarto Sugiarto (STAI Hubbulwathan Duri, 2022)
The purpose of the study was to determine the application of limited face-to-face learning policies in schools in the DKI Jakarta area. This policy emerged through a study of the impact of online learning and also the reduction in the transmission rate of the Covid-19 virus. So, the gap in this research is the understanding of the concept of implementing government policies regarding face-to-face learning is limited. The research method used is qualitative through a survey. The object of observation to examine this limited face-to-face learning is from Early Childhood Education to Senior High School. Data collection techniques using observation, interviews, and documents. data analysis technique consists of stages of data collection, data reduction, data presentation, and concluding. The validity of the data consists of credibility, transferability, dependability, and confirmability. The results showed that the implementation of the limited face-to-face learning policy was by the results of the study of the condition of the spread of the covid-19 virus, the results of discussions with schools, and also the results of input from parents. The implementation of limited face-to-face learning is carried out with careful planning, directed, and routinely evaluating learning activities by minimizing the obstacles experienced during limited learning activities.